2021
DOI: 10.3390/ijms22136681
|View full text |Cite
|
Sign up to set email alerts
|

Six Decades of Research on Human Fetal Gonadal Steroids

Abstract: Human fetal gonads acquire endocrine steroidogenic capabilities early during their differentiation. Genetic studies show that this endocrine function plays a central role in the sexually dimorphic development of the external genitalia during fetal development. When this endocrine function is dysregulated, congenital malformations and pathologies are the result. In this review, we explain how the current knowledge of steroidogenesis in human fetal gonads has benefited from both the technological advances in ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 139 publications
1
10
0
Order By: Relevance
“…Interestingly, human scRNASeq data suggest that only a small subset of human fetal Leydig cells produce androgen precursors between weeks 14–18 of gestation [ Supplementary Figure 1 ( 35 )]. This speculation is aligned with evidence that human fetal interstitial and Leydig-like cells are a heterogenous population ( 49 ).…”
Section: Learning About Androgen Biosynthesis In the Fetal Testissupporting
confidence: 72%
See 2 more Smart Citations
“…Interestingly, human scRNASeq data suggest that only a small subset of human fetal Leydig cells produce androgen precursors between weeks 14–18 of gestation [ Supplementary Figure 1 ( 35 )]. This speculation is aligned with evidence that human fetal interstitial and Leydig-like cells are a heterogenous population ( 49 ).…”
Section: Learning About Androgen Biosynthesis In the Fetal Testissupporting
confidence: 72%
“…The first trimester human testes can produce low levels of T via the Δ4 pathway prior to a switch to the Δ5 pathway at the beginning of the second trimester ( 48 ). Thereafter, the human fetal testis produces high levels of T during the second trimester via the classical Δ5 steroidogenic pathway ( Figure 1B , blue lines) ( 48 , 49 ). This switch coincides with the maturation of fetal Leydig cells as they acquire their capacity to produce androgen precursors ( 48 ).…”
Section: Learning About Androgen Biosynthesis In the Fetal Testismentioning
confidence: 99%
See 1 more Smart Citation
“…About 95% of T is produced and secreted by Leydig cells in the testis, and the remaining 5% is produced in adrenal glands by conversion of precursors (e.g., DHEA, DHEA sulfate, and androstenedione) [18]. T is converted to DHT and 17β-estradiol (E2, the main active estrogen), by the enzymes 5α-reductase (SRD5A) and aromatase, respectively [18,29]. There are three different isoforms of SRD5A, encoded by separate genes (SRD5A1, SRD5A2, and SRD5A3) and, among these, the most prevalent and biologically active isoenzyme is the SRD5A1.…”
Section: Sex Steroid Hormones (Androgens)mentioning
confidence: 99%
“…Several experimental studies have demonstrated the endocrine disrupting capacity of APAP in fetal testis ( 5-8 ). Although studies showed that elements of the steroidogenic pathway are present in the human fetal ovary (hFO) ( 9-12 ) and that it displays endocrine activity ( 13 ), the effect of APAP on fetal ovarian endocrine capability has not been reported.…”
mentioning
confidence: 99%